A review: crystalline silicon membranes over sealed cavities for pressure sensors by using silicon migration technology *Project supported by the National Major Science & Technology Program of China (No. 2011ZX02507-001). (July 2018) - Su, Jiale; Zhang, Xinwei; Zhou, Guoping; Xia, Changfeng; Zhou, Wuqing; Huang, Qing'an
Abstract: A silicon pressure sensor is one of the very first MEMS components appearing in the microsystem area. The market for the MEMS pressure sensor is rapidly growing due to consumer electronic applications in recent years. Requirements of the pressure sensors with low cost, low power consumption and high accuracy drive one to develop a novel technology. This paper first overviews the historical development of the absolute pressure sensor briefly. It then reviews the state of the art technology for fabricating crystalline silicon membranes over sealed cavities by using the silicon migration technology in detail. By using only one lithographic step, the membranes defined in lateral and vertical dimensions can be realized by the technology. Finally, applications of MEMS through using the silicon migration technology are summarized.